2012
DOI: 10.1016/j.ijoa.2012.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and preterm fetal sheep responses to dexmedetomidine

Abstract: Background The α2 adrenergic receptor agonist dexmedetomidine has some unique pharmacologic properties that could benefit pregnant patients (and their fetuses) when they require sedation, analgesia, and/or anesthesia during pregnancy. The purpose of the present study was to delineate maternal and fetal responses to an intravenous infusion of dexmedetomidine. Methods This study was conducted on surgically-recovered preterm sheep instrumented for physiologic recording and blood sampling. Maternal and fetal car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Dexmedetomidine has a high placental retention [ 21 ]. It has shown no significant effect on fetal HR, MAP, blood gas, or cerebral oxygenation in an animal study with pregnant sheep subjected to preterm surgical deliveries [ 22 ]. El-Tahan et al [ 18 ] found that Apgar scores, Neurologic and Adaptive Capacity Scores, and acid-base status were similar between the control and the neonates born to mothers receiving preoperative dexmedetomidine 0.2–0.6 μg/kg/h over 20 min.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine has a high placental retention [ 21 ]. It has shown no significant effect on fetal HR, MAP, blood gas, or cerebral oxygenation in an animal study with pregnant sheep subjected to preterm surgical deliveries [ 22 ]. El-Tahan et al [ 18 ] found that Apgar scores, Neurologic and Adaptive Capacity Scores, and acid-base status were similar between the control and the neonates born to mothers receiving preoperative dexmedetomidine 0.2–0.6 μg/kg/h over 20 min.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant sheep and their fetuses are commonly utilized as animal models for investigations into human pregnancy and the causes and consequences of preterm birth. [1][2][3][4] As elegantly argued in Russell and Burch's landmark work, The principles of humane experimental technique, the continual refinement of practice in animal-based research is key to minimizing the impact of research on animal welfare and to ensuring the integrity of scientific data. 5 General anaesthesia causes major physiological alterations to the respiratory, cardiovascular, neurological, immune and endocrine systems and specific considerations exist for anaesthesia of pregnant patients.…”
mentioning
confidence: 99%
“…On the day of surgery, general anesthesia was induced from 07:00 by intramuscular administration of 0.2 mg/kg xylazine (Bayer Yakuhin Ltd., Osaka City, Japan). Subsequently, 3 mg/kg/min dexmedetomidine hydrochloride (Maruishi Pharmaceutical Co., Ltd., Osaka City, Japan) [ 36 ] was administered via a peripheral intravenous line on the front right leg of the sheep obtained after xylazine administration. Acetaminophen (Terumo Co., Ltd., Tokyo, Japan) (1,000 mg/body/30 min) and antibiotics (1 g flomoxef sodium/body; biological half-life: 49.2 min; Shionogi Co., Ltd., Tokyo, Japan) were intravenously administered before surgery to control surgical pain and surgical site infection, respectively.…”
Section: Methodsmentioning
confidence: 99%